Própolis vermelha e L-Lisina inibindo angiogênese no Tumor de Walker em modelo de bolsa jugal de hamster - Juanes, Camila de Carvalho (2018)
Angiogenesis is the formation of new blood vessel from pre-existing vessels. Angiogenesis is a process that takes part in the progression of cancer. It is also plays a role in several diseases, including diabetic retinopathy and rheumatoid arthritis. This study, aimed to evaluate the propolis and L-lysine effect in tumor angiogenesis and Walker carcinosarcoma in hamster cheek pouch. Fifty-seven animals were divided into eight groups. The groups I, II, III and IV (red propolis – 200 mg/5 ml/kg -, L-lysine – 150 mg/kg -, arabic gum 1% - 5 ml/kg - and water - 5 ml/kg -, respectively) were treated ten days after tumor inoculation. The groups V, VI, VII and VIII (red propolis – 200 mg/5 ml/kg -, L-lysine – 150 mg/kg -, arabic gum 1% - 5 ml/kg - and water - 5 ml/kg -, respectively) were treated 33 days before and ten days after tumor inoculation. The angiogenesis was assessed by determining the mean vascular area AVm, in pixels (px) and percentage terms (%). The size of the tumor was assessed by determining the tumor area (ATu) and perimeter (PTu) in a single plane. The AVm (px) of group I (p < 0,05) and of group II (p < 0,001) was significantly lower than in of group IV, and AVm (%) of group II (p < 0,01) was significantly lower than in of group IV. There was no significant differences of AVm (px) (F = 1,6958; p = 0,1957) and AVm (%) (F = 1,7242; p = 0,1900) between the groups V, VI, VII and VIII. There was no significant difference of ATu (F = 1,6231; p = 0,2156) and PTu (F = 0,7818; p = 0,5180) between the groups I, II, III and IV. There was no significant differences of ATu (F = 1,3891; p = 0,2713) between the groups V, VI, VII e VIII, and there was no significant difference of PTu between experimental and control groups. Propolis and L-lysine inhibited tumor angiogenesis, when given after the tumor inoculation, at the doses and times administered.